Cover Feature: Aromatic Thioethers as Novel Luminophores with Aggregation‐Induced Fluorescence and Phosphorescence (Chem. Eur. J. 55/2017). Issue 55 (21st August 2017) - Riebe, Steffen; Vallet, Cecilia; van der Vight, Felix; Gonzalez‐Abradelo, Dario; Wölper, Christoph; Strassert, Cristian A.; Jansen, Georg; Knauer, Shirley; Voskuhl, Jens
Abstract : The synthesis of a library of aromatic thioethers led to novel luminophores with aggregation‐induced emission properties. It was found that the substitution pattern as well as the introduction of different functional groups has a direct influence on the photophysical properties. A remarkable broad range of emission (437–588 nm) was obtained. Besides fluorescence also long‐lived excited states (up to 5 μs), termed phosphorescence were observed. This easy to synthesize, non‐toxic class of compounds enables further applications in material sciences, as well as for biomedical applications, such as bio‐imaging. More information can be found in the Full Paper by J. Voskuhl et al. onpage 13660 .